Digital Transformation for Smart and Resilient Cities: Assessing Platform Maturity and ISO 37123 Compliance - Daiane Maria de Genaro Chiroli; Thallita Puzi Ferrassa; Leticia do Nascimento Idalgo; Marcela Marçal Alves Pinto Mick; João Luiz Kovaleski; Franciely Velozo Aragão; Sergio Mazurek Tebcherani; Fernanda Cavicchioli Zola (Platforms)
This paper explores the transformative potential of digital platforms in fostering resilient and intelligent urban environments, a critical need considering rapid urbanization and climate change. Through a comparative analysis of various digital platforms in global cities, this study identifies their role in enhancing operational efficiency, participatory governance, and urban innovation. Utilizing a structured maturity model based on the ISO 37123 standard for resilient communities, this research highlights the specific challenges faced by cities at different stages of digital transformation and provides practical recommendations for implementing digital solutions that integrate resilience, sustainability, and smart governance. The analysis underscores the importance of aligning digital platform development with the United Nations Sustainable Development Goals (SDGs), offering a pathway for cities to enhance resilience, optimize resource use, and promote citizen engagement.